NUTRITIONAL PROFILE OF ADOLESCENT FEMALE ATHLETES AT QUEEN MARY'S COLLEGE, CHENNAI - PUNITHA, (International Journal of Pharma and Bio Sciences, 2016)
Adequate nutrition is important for the proper growth and development of young people. It is even more essential to the competitive youth athlete, With the higher demands of strenuous training and competition, proper diet is crucial not only to insure optimal performance, but also to prevent developmental problems, which may have lifelong effects. Nutritional requirements of athlete’s adolescent girl increase according to their various physical performance. The main aim of the study to assess the Nutritional profile of adolescent female athletes through nutritional anthropometric measurements such as body weight, height and body mass index, waist circumference and hip circumference measurements. The study was conducted among 50 adolescent female adolescent athletes (18-21 years old were selected. Results of the physical fitness tests revealed that 50 % had good flexibility, 56% had good coordination, 40% had excellent equilibrium and 38% had good score for speed test. Diets consisted of low energy, protein and low carbohydrate intake were adequate.